2020
DOI: 10.1007/s40843-020-1469-2
|View full text |Cite
|
Sign up to set email alerts
|

超细PtCu纳米线的表面结构调控及其增强的醇类 电催化氧化作用

Abstract: Surface tailoring of Pt-based nanocatalysts is an effective pathway to promote their electrocatalytic performance and multifunctionality. Here, we report two kinds of one-dimensional (1D) ultrafine PtCu nanowires (smooth surface & rugged surface) synthesized via a wet chemical method and their distinct catalytic performances in electrooxidation of alcohols. The alloyed PtCu nanowires having rough surfaces with atomic steps exhibit superior catalytic activity toward multiple electrochemical reactions compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Among the shape‐controlled nanocatalysts, multimetallic nanoparticles with high‐index facets (HIFs) have attracted much attention owing to their low‐coordinated surface atoms that exhibit enhanced activity for several electrocatalysis. [ 47 , 48 ] However, the instability of the facets makes it difficult for the facets to survive under reaction conditions. While extensive progress has been made in the fabrication and systematic studies on monometallic systems with HIF, there are very few studies for multimetallic systems, owing to the higher complexity compared to monometallic systems.…”
Section: Synthetic Methods For Various Nmmnsmentioning
confidence: 99%
“…Among the shape‐controlled nanocatalysts, multimetallic nanoparticles with high‐index facets (HIFs) have attracted much attention owing to their low‐coordinated surface atoms that exhibit enhanced activity for several electrocatalysis. [ 47 , 48 ] However, the instability of the facets makes it difficult for the facets to survive under reaction conditions. While extensive progress has been made in the fabrication and systematic studies on monometallic systems with HIF, there are very few studies for multimetallic systems, owing to the higher complexity compared to monometallic systems.…”
Section: Synthetic Methods For Various Nmmnsmentioning
confidence: 99%
“…At present, PtCu binary metal catalyst has attracted great attention of scientists due to its good oxidation activity, stability and anti-poisoning performance for methanol of direct methanol fuel cells (DMFCs), and many research groups have achieved excellent results [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Chen et al [10] have found that hollow PtCu octahedral nanoalloys are e cient bifunctional electrocatalysts towards oxygen reduction reaction and methanol oxidation reaction by regulating near-surface composition.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous efforts have been made to demonstrate that Pt-based catalysts are promising candidates for ethanol electrooxidation. However, their catalytic activity and stability urgently need to be improved for enabling commercial deployment of DEFCs. To improve catalytic efficiency, one effective approach is to conduct surface engineering to increase the number of active sites, through dispersing Pt atoms on the catalyst surface to form Pt-skin layers, or constructing defect-rich surface to fully expose Pt active sites. Another strategy is to enhance the intrinsic reactivity of each active site, which can be achieved by control over the strain effect of catalyst surface via strain engineering. However, Pt-skin layers and defect-rich surface over alloy nanoparticles are usually destroyed during long-term catalytic operation due to structural rearrangement induced by the segregation and dealloying process, resulting in the decrease of activity and poor durability. Intermetallic compounds with atomically ordered arrangements and well-defined stoichiometry possess excellent structural stability. Therefore, rational design of Pt-based intermetallic compounds via surface engineering and strain engineering is expected to enhance electrocatalytic activity while maintaining superior durability; however, it still remains a grand challenge.…”
mentioning
confidence: 99%